2009
DOI: 10.1542/peds.2008-1619
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Births Are a Risk Factor for Postpartum Maternal Depressive Symptoms

Abstract: Mothers of multiple births had 43% greater odds of having moderate/severe, 9-month postpartum, depressive symptoms, compared with mothers of singletons. Greater attention is needed in pediatric settings to address maternal depression in families with multiple births.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 48 publications
4
71
1
3
Order By: Relevance
“…The objectives of the studies under analysis were to identify variables that influenced the quality of life of parents, 24 focusing in particular on mental health, 29,31,[35][36] psychosocial well-being 26,30 and parental stress. 23,26,37,[40][41] They also covered marital adaptation, 29,32-33 parental adjustment 25,32 and behavior 25 and development of children, 28,30 seeking to identify the determining factors of this process 23,[27][28][29][30][33][34][37][38]40 and using twinning parenthood as a reference.…”
Section: Social Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…The objectives of the studies under analysis were to identify variables that influenced the quality of life of parents, 24 focusing in particular on mental health, 29,31,[35][36] psychosocial well-being 26,30 and parental stress. 23,26,37,[40][41] They also covered marital adaptation, 29,32-33 parental adjustment 25,32 and behavior 25 and development of children, 28,30 seeking to identify the determining factors of this process 23,[27][28][29][30][33][34][37][38]40 and using twinning parenthood as a reference.…”
Section: Social Supportmentioning
confidence: 99%
“…From the comparative analyses used in some of the research, we considered the difference between groups, taking into account: different types of conception, [25][26]32,[36][37] number of births per pregnancy [26][27][28][30][31][32][33][35][36]38,41 and gestation period. 29,38 …”
Section: Social Supportmentioning
confidence: 99%
“…In a controlled research in the US, between 2001 and 2002, the data of 7293 infants and 776 mothers of twins were analyzed and compared. Nine months after delivery, 43% of the mothers of twins had a greater chance of obtaining moderate or severe symptoms of depression than mothers of a single infant (Choi et al, 2009). Examining single deliveries, O'Hara et al (1990) found that the rate for depression periods accounted for 10%-20% in the first six months after delivery.…”
Section: Discussionmentioning
confidence: 99%
“…(5) The demands of the parent role is even greater with twin children, and in this sense, research indicates that mothers of twins report difficult experiences more frequently, and present higher levels of stress and symptoms of depression. (6)(7)(8) In families with twins, role renegotiation and work reorganization take on particular relevance for the couple, for taking care of two or more children of the same age and with the same needs becomes a taxing job that is almost impossible for one person to accomplish alone. The demands of twin children can bring multiple vulnerabilities and difficulties to the families, on the level of daily management, as well as increasing the family's financial needs and making it challenging to have a social life.…”
Section: Introductionmentioning
confidence: 99%
“…The demands of twin children can bring multiple vulnerabilities and difficulties to the families, on the level of daily management, as well as increasing the family's financial needs and making it challenging to have a social life. (8,9) When families are cared for within a reductionist view, centred on fragmentation of care, this leads to a lack of comprehensiveness which contributes to a more difficult parenting experience. It is important to care for these families within an efficient, comprehensive and longitudinal framework.…”
Section: Introductionmentioning
confidence: 99%